Integración de la Energías Renovables No Convencionales (ERNC) en el Mercado Eléctrico peruano: Cambios en el diseño de mercado de corto plazo de Energía y Servicios Complementarios (SSCC) - Rojas Jaen, Juan Paul Elias (2024)
The purpose of this paper is to present the regulatory schemes necessary for an efficient and reliable penetration of Non-Conventional Renewable Energy (NCRE) in the Peruvian electricity market, proposing a broadly defined regulatory proposal, as well as the main advantages and disadvantages found. For this aim, the main regulatory schemes of the relevant countries are defined, and the reasons for one election or another regulatory option are explained. The methodology consists of the review of primary and secondary source documents related to the way in which the problems of NCRE integration are solved in the relevant countries. Also, the realization or presentation of calculations of the Peruvian economic dispatch data, including primary and secondary sources, contained in Annex No. 5 of this document. From this review, it is concluded that of the pricing schemes in the shortterm markets, the Day Ahead, Intraday and Real Time markets are widely more used than the audited cost markets (only used in Chile, from the sample chosen). Furthermore, since greater integration of renewable energy requires greater use of Ancillary Services (AC), the selected countries opt to use Day-Ahead and Real- Time Market schemes for the economic dispatch of energy and AC, including the inclusion of new products such as ramp and fast start-up. Opting for Day-Ahead, Intraday and Real-Time dispatch schemes is more consistent with the variable and uncertain nature of NCRE, as uncertainty is reduced the closer the time is to the dispatch itself, as well as the binding nature of the submitted offer. It also allows the application of the Causality Principle in the apportionment of payments for AC, giving correct price signals by internalizing the higher costs of AC originating in the higher demand for AC due to the entry of renewable energy.